Crosslinker-free silk/decellularized extracellular matrix porous bioink for 3D bioprinting-based cartilage tissue engineering - Zhang, Xiao; Liu, Yang; Luo, Chunyang; Zhai, Chenjun; Li, Zuxi; Zhang, Yi; Yuan, Tao; Dong, Shilei; Zhang, Jiyong; Fan, Weimin (Materials Science & Engineering C, 2021)
As cartilage tissue lacks the innate ability to mount an adequate regeneration response, damage to it is detrimental to the quality of life of the subject. The emergence of three-dimensional bioprinting (3DBP) technology presents an opportunity to repair articular cartilage defects. However, widespread adoption of this technique has been impeded by difficulty in preparing a suitable bioink and the toxicity inherent in the chemical crosslinking process of most bioinks. Our objective was to develop a crosslinker-free bioink with the same biological activity as the original cartilage extracellular matrix (ECM) and good mechanical strength. We prepared bioinks containing different concentrations of silk fibroin and decellularized extracellular matrix (SF-dECM bioinks) mixed with bone marrow mesenchymal stem cells (BMSCs) for 3D bioprinting. SF and dECM interconnect with each other through physical crosslinking and entanglement. A porous structure was formed by removing the polyethylene glycol from the SF-dECM bioink. The results showed the SF-dECM construct had a suitable mechanical strength and degradation rate, and the expression of chondrogenesis-specific genes was found to be higher than that of the SF control construct group. Finally, we confirmed that a SF-dECM construct that was designed to release TGF-β3 had the ability to promote chondrogenic differentiation of BMSCs and provided a good cartilage repair environment, suggesting it is an ideal scaffold for cartilage tissue engineering. •A crosslinked-free silk-dECM gel is printable and cytocompatible.•PEG induces the formation of β-sheet and act as a porogen.•Physical crosslinking and entanglement provide good mechanical strength.•Silk-dECM construct enhanced chondrogenesis of BMSCs.•The construct supports the controlled release of chondrogenic growth factors.